2017
DOI: 10.1161/circimaging.116.005670
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Myocardial Function, Body Mass Index, and Outcome After ST-Segment–Elevation Myocardial Infarction

Abstract: Background-Better survival for overweight and obese patients after ST-segment-elevation myocardial infarction (STEMI) has been demonstrated. The association between body mass index (BMI), outcome, and left ventricular (LV) structure and function after STEMI, including LV longitudinal strain (global longitudinal strain), was evaluated. . LV global longitudinal strain was measured using speckle-tracking analysis. Primary outcome measure was all-cause mortality. Compared with normal/underweight patients, obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Moscarella et al [27] stated that after a 5-year follow-up period 9.5% of overweight patients were dead, slightly more patients with BMI < 25 -13.7% and the smallest number of obese patients with STEMI -6.3%. Joyce et al [29] noted similar results obtained during a 5-year follow-up of patients after STEMI, as 13.6% of patients who were underweight or had normal body weight, and 9.1% of overweight and obese patients died.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moscarella et al [27] stated that after a 5-year follow-up period 9.5% of overweight patients were dead, slightly more patients with BMI < 25 -13.7% and the smallest number of obese patients with STEMI -6.3%. Joyce et al [29] noted similar results obtained during a 5-year follow-up of patients after STEMI, as 13.6% of patients who were underweight or had normal body weight, and 9.1% of overweight and obese patients died.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study overweight patients constitute the biggest group (45%), people with normal body weight represent 35%, 12.5% of patients from the tested group were obese, while 7.5% of patients were underweight. Joyce et al [29] reported that 51% of patients were overweight, 30% had normal body weight, and 19% people were obese. Similarly, in the study by Moscarella et al [27], overweight patients amounted to nearly half (49.4%) of the group with NSTEMI, obese patients -22.4% and people with normal BMI -28.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 2,040 records were excluded as a result of irrelevant content. Finally, a total of 65 records met the eligibility criteria and provided sufficient data to be included in the current NMA . A flow diagram of the literature selection process is listed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fifth, the present Japanese AMI cohort included a limited number of patients with extremely high BMI (≥40 kg/m 2 ), although a previous AMI study in a Western country demonstrated higher mortality not only in underweight patients but also in patients with extremely high BMI (U-shaped relationship between BMI and mortality). 33 Sixth, we only collected the BMI data at the time of study registration; any change in the BMI was not evaluated, therefore, we could not discuss the effect of BMI change on the clinical outcomes. Finally, these results were derived from only Japanese populations, and therefore might not be generalizable to other populations.…”
Section: Discussionmentioning
confidence: 99%